Tie-breaking in social network search algorithm for software test redundancy reduction optimization problem - Mekeng, Ambros Magnus Rudolf; Kamal Z., Zamli; Muhammad Zarlis, .; Muhammad Arif, Mohamad; Darusalam, Ucuk (IEEE, 2026)
Test Redundancy Reduction (TRR) is an important approach for minimizing the number of test cases while still satisfying all user acceptance test requirements. During the TRR optimization process, situations may arise in which multiple candidate solutions exhibit identical fitness values, leading to ambiguity in solution selection. To address this issue, tie-breaking mechanisms, namely first-element tiebreaking, last-element tie-breaking, and random tie-breaking can be applied, each employing a distinct strategy to resolve equal-fitness solutions. In this study, the Social Network Search (SNS) algorithm is employed to investigate the impact of these tie-breaking mechanisms on TRR optimization performance, motivated by the No Free Lunch (NFL) theorem, which states that no single optimization algorithm performs best across all problems. The experimental evaluation focuses on identifying solutions that achieve full requirement coverage (100%) with the minimum possible number of test cases. Experimental results demonstrate that the SNS algorithm integrated with tie-breaking mechanisms consistently achieves optimal fitness, attaining 100% requirement coverage, and the tie-breaking also effect to runtime.